New Octopus‐like Phthalocyanines as Fullerene Receptors: Synthesis and Photophysical Investigation. Issue 2 (21st July 2015) - Nefedova, Irina V.; Martynov, Alexander G.; Averin, Alexey A.; Kirakosyan, Gayane A.; Tsivadze, Aslan Yu.; Gorbunova, Yulia G.
Abstract: Octopus‐like zinc and magnesium phthalocyaninates bearing eight flexible benzylated diethylene glycol chains were synthesized and their interaction with fullerenes C60 and C70 was investigated by UV‐Vis spectrophotometric titration, as well as by steady‐state and time‐resolved fluorescence spectroscopy in chloroform and toluene media. These measurements revealed a high affinity of receptors for C60 and C70, with selectivity to C70 : binding constants for C70 are almost two times higher than for C60 . These results are interpreted by means of quantum‐chemical calculations using the PM6‐DH2 Hamiltonian. The binding constants also depend on both the nature of the metal ion in the receptor and the solvent. It is expected that the obtained molecules and supramolecular complexes can be used for further elaboration of optoelectronic donor‐acceptor materials. Abstract :